Perspectives: On the Historicalness of Sign Languages - Cantin, Yann; Encrevé, Florence (Frontiers in Communication, 2022)
This paper aims to provide a reflection on an assumption sometimes present in linguistic research: the supposed youth of sign languages (SLs) (e.g., Meier, 2002: 6). In this research (the importance of which we do not question), SLs are considered to date back to the mid-eighteenth century (Fischer, 2015: 445), or the mid- twentieth century (Sandler, et al., 2005: 2261). As historians, we wish to question this hypothesis. To this end, we will question the scientific consequences of a reversal of this hypothesis. The historical method used forbids presenting a hypothesis as a postulate until it has been validated by sources, whose authenticity can be granted. In order to illustrate this, we will take the example of the French sign language: from a historical point of view, sources attest that its roots go back at least to the early Middle Ages (Cantin, 2016; Cantin, 2021). It would therefore be an old language, at least as old as French (Cantin, Encrevé, & L'Huillier, 2019). From this case, we would like to propose a new hypothesis: that the sign languages of the world are not young. And we would like linguists to consider the possibility for the SL they are studying to be an old language. Would this new paradigm change previous conclusions (cf. Cuxac and Antinoro Pizzuto, 2010; Garcia, 2021)? To what extent would this allow for a renewal, for example opening the way to another perspective on the genesis of these languages (Cuxac and Sallandre, 2007; Garcia and Sallandre 2020)?